Efficacy Differences of Platelet Rich Plasma for Treatment of Androgenetic Alopecia between Men and Women - Rubab Anjum, Tahir Hassan, Muhammad Khurram Shahzad, Nazia Hanif, Zunaira Anjum, Gul-E- Rukh (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Almost 50% males face a health issue called androgenic alopecia and even almost 21 million women are affected too. Aim: To determine the efficacy difference of platelet rich plasma for treatment of androgenic alopecia among patients. Study design: Quasi experimental method. Methodology: In order to collect the data, the purposive sampling technique was used. Enrolled patients (n=102) were divided into two groups. Each group received PRP infections after every 1 month for 3 months. Follow up was done at 3 and 6 months. Results were assessed by standard photographs and Hamilton Norwood scale for men and Ludwig scale for women. SPSS v 23 evaluated data. Chi-square test was used to compare the efficacy of Platelet Rich Plasma for treatment of androgenic alopecia between genders. Results: Mean age of the study participants was 27.1±4.5 years. Independent sample t test revealed that the mean age of the female participants was significantly higher than male participants (p < 0.001). There was 100% response rate of PRP treatment for androgenic alopecia in both genders. Practical Implication: This study helped researchers in exploring the efficacy of PRP as a remedy for hair re-growth as it is cheap and safe. Secondly, it added to local literature regarding androgenic alopecia. Conclusion: It was concluded that sub-dermal PRP injections were effective among both genders with androgenic alopecia. Keywords: Efficacy, Androgenic alopecia, Response Rate, Treatment Options and Plasma Rich Proteins.